The role of gastric microecological dysbiosis in gastric carcinogenesis - Huang, Hui; Zhong, Wei; Wang, Xiaojiao; Yang, Ying; Wu, Tianmu; Chen, Runyang; Liu, Yanling; He, Feng; Li, Jun (Frontiers in Microbiology, 2023)
Gastric cancer (GC) is the leading cause of cancer-related death worldwide, and reducing its mortality has become an urgent public health issue. Gastric microecological dysbiosis (including bacteria, fungi, viruses, acid suppressants, antibiotics, and surgery) can lead to gastric immune dysfunction or result in a decrease in dominant bacteria and an increase in the number and virulence of pathogenic microorganisms, which in turn promotes development of GC. This review analyzes the relationship between gastric microecological dysbiosis and GC, elucidates dynamic alterations of the microbiota in Correa's cascade, and identifies certain specific microorganisms as potential biomarkers of GC to aid in early screening and diagnosis. In addition, this paper presents the potential of gastric microbiota transplantation as a therapeutic target for gastric cancer, providing a new direction for future research in this field.